Hybrid Learning Readiness: Techno Pedagogical Skills and Digital Competence Education - Ika Korika Swasti; Endang Sholihatin (Future Science, 2022)
This study aims to examine techno-pedagogical skills to realize digital competence in the hybrid learning process. This study used a case study method, collecting data through questionnaires and in-depth interviews (FGD) from informants and a sample of 35 people. The research location is at UPN